Mental disorders and risk of COVID-19-related mortality, hospitalisation, and intensive care unit admission: a systematic review and meta-analysis. (September 2021) - Vai, Benedetta; Mazza, Mario Gennaro; Delli Colli, Claudia; Foiselle, Marianne; Allen, Bennett; Benedetti, Francesco; Borsini, Alessandra; Casanova Dias, Marisa; Tamouza, Ryad; Leboyer, Marion; Benros, Michael E; Branchi, Igor; et al.
Summary: Background: Mental disorders might be a risk factor for severe COVID-19. We aimed to assess the specific risks of COVID-19-related mortality, hospitalisation, and intensive care unit (ICU) admission associated with any pre-existing mental disorder, and specific diagnostic categories of mental disorders, and exposure to psychopharmacological drug classes. Methods: In this systematic review and meta-analysis, we searched Web of Science, Cochrane, PubMed, and PsycINFO databases between Jan 1, 2020, and March 5, 2021, for original studies reporting data on COVID-19 outcomes in patients with psychiatric disorders compared with controls. We excluded studies with overlapping samples, studies that were not peer-reviewed, and studies written in languages other than English, Danish, Dutch, French, German, Italian, and Portuguese. We modelled random-effects meta-analyses to estimate crude odds ratios (OR) for mortality after SARS-CoV-2 infection as the primary outcome, and hospitalisation and ICU admission as secondary outcomes. We calculated adjusted ORs for available data. Heterogeneity was assessed using the I 2 statistic, and publication bias was tested with Egger regression and visual inspection of funnel plots. We used the GRADE approach to assess the overall strength of the evidence and the Newcastle Ottawa Scale to assess study quality. We also did subgroup analyses and meta-regressions to assess the effects of baseline COVID-19 treatment setting, patient age, country, pandemic phase, quality assessment score, sample sizes, and adjustment for confounders. This study is registered with PROSPERO, CRD42021233984. Findings: 841 studies were identified by the systematic search, of which 33 studies were included in the systematic review and 23 studies in the meta-analysis, comprising 1 469 731 patients with COVID-19, of whom 43 938 had mental disorders. The sample included 130 807 females (8·9% of the whole sample) and 130 373 males (8·8%). Nine studies provided data on patient race and ethnicity, and 22 studies were rated as high quality. The presence of any mental disorder was associated with an increased risk of COVID-19 mortality (OR 2·00 [95% CI 1·58–2·54]; I 2 =92·66%). This association was also observed for psychotic disorders (2·05 [1·37–3·06]; I 2 =80·81%), mood disorders (1·99 [1·46–2·71]; I 2 =68·32%), substance use disorders (1·76 [1·27–2·44]; I 2 =47·90%), and intellectual disabilities and developmental disorders (1·73 [1·29–2·31]; I 2 =90·15%) but not for anxiety disorders (1·07 [0·73–1·56]; I 2 =11·05%). COVID-19 mortality was associated with exposure to antipsychotics (3·71 [1·74–7·91]; I 2 =90·31%), anxiolytics (2·58 [1·22–5·44]; I 2 =96·42%), and antidepressants (2·23 [1·06–4·71]; I 2 =95·45%). For psychotic disorders, mood disorders, antipsychotics, and anxiolytics, the association remained significant after adjustment for age, sex, and other confounders. Mental disorders were associated with increased risk of hospitalisation (2·24 [1·70–2·94]; I 2 =88·80%). No significant associations with mortality were identified for ICU admission. Subgroup analyses and meta-regressions showed significant associations of baseline COVID-19 treatment setting (p=0·013) and country (p<0·0001) with mortality. No significant associations with mortality were identified for other covariates. No evidence of publication bias was found. GRADE assessment indicated high certainty for crude mortality and hospitalisation, and moderate certainty for crude ICU admission. Interpretation: Pre-existing mental disorders, in particular psychotic and mood disorders, and exposure to antipsychotics and anxiolytics were associated with COVID-19 mortality in both crude and adjusted models. Although further research is required to determine the underlying mechanisms, our findings highlight the need for targeted approaches to manage and prevent COVID-19 in at-risk patient groups identified in this study. Funding: None. Translations: For the Italian, French and Portuguese translations of the abstract see Supplementary Materials section.